Partnerships blending institutional logics for inclusive global and regional food value chains in Ghana; with what smallholder effect? - Paassen, Annemarie van; Osei-Amponsah, Charity; Klerkx, Laurens; Mierlo, B. van; Essegbey, G. O. (Springer, 2022)
We witness a promotion of hybrid partnerships, where actors with different competences and resources collaborate for smallholder inclusive value chain development. To better understand the functioning of these partnerships, we used institutional theory and studied the context of a global and emerging regional food value chains in Ghana, the blending of logics by key actors in Innovation Platforms and Public Private Partnerships, and their effect on value chain relations of smallholder farmers. In the global value chain of cocoa, partnerships adhered to ‘green revolution’ and ‘free-market’ logics, and provided all farmers material support. In the more informally organised regional food sector, local executing partners selectively coupled their logics with those of poor smallholders, who rely on low-input agriculture and solidarity logics to make ends meet. This improved the position and transaction costs of smallholders to participate in the value chain. Hence, it is more likely for partnerships to create smallholder inclusive governance in informally organised regional food value chains, than highly structured global value chains controlled by international buyers. To gain insight in the variety of political effects this triggers in different social–historical shaped farmer communities, households and actors, we recommend complementary local research from a critical institutional perspective.